Width of buccal and posterior corridors: differences between cases treated with asymmetric and symmetric extractions - Castello Branco,Nuria Cabral (2012)
OBJECTIVE: To verify if there is difference in the buccal and posterior corridor width in cases treated with extraction of one and four premolars. METHODS: Through posed smile photographs of 23 Class II patients, subdivision, treated with extraction of one premolar and 25 Class I and Class II patients, subdivision, treated with extraction of four premolars, the percentage of buccal and posterior corridor width was calculated. The two protocols of extractions were compared regarding the buccal and posterior corridor width by independent t tests. RESULTS: There was no statistically significant difference on the buccal and posterior corridor widths between patients treated with symmetric and asymmetric extraction. CONCLUSION: The buccal and posterior corridor did not differ between the evaluated protocols of extractions.